PROBLEMS FACED IN SPEAKING ASSESMENT DURING THE COVID-19 PANDEMIC. STUDY CASE OF UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR. - Diana, Laksmi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The education sector is one of the areas that was badly affected during the Covid-19 pandemic, where all schools and campuses in Indonesia have been closed and learning is carried out online. There are impacts from having online learning experienced by students and teachers or lecturers. This study examines the problems that arise during the assessment of speaking skill as one of the skills that students must have in English language skills, which was carried out in English classes during the Covid-19 pandemic. Speaking skill is considered as the most difficult language skill in Indonesia. There are several criteria for determining the categories of problems that arise during the assessment.